IMPLEMENTATION OF LED-PHOTODIODE SENSOR AS ONE OF THE INDICATORS OF TURBIDITY MEASUREMENT IN IOT-BASED UTILITY WATER QUALITY MONITORING SYSTEM - Rizal Maulana; Muhammad Dhany Wahyudi Saputra; Suyatno Suyatno; Iim Fatimah (Instrumentasi, 2025)
Although water is a vital element for human life, access to it in Indonesia remains limited due to population growth and uneven distribution. Indonesia faces the threat of water crisis despite having abundant resources due to pollution from domestic waste as well as agricultural and industrial sectors. This study directs attention to the development of an IoT-based water quality monitoring system that utilizes led-photodiodes as indicators to detect water turbidity online in combination with pH sensors and TDS sensors. The performance analysis of the TDS sensor showed an average error of 5% with an accuracy rate of 95% and a standard deviation recorded at 2.27. The turbidity sensor showed an average error of 60% with an accuracy of 40% and a standard deviation of 8.83, operating optimally in the turbidity range of 30-160 NTU but its accuracy decreased at very low or high NTU values. The pH sensor recorded an average error of 9% with an accuracy of 91% and showed a standard deviation of 0.17. This research showcases the system built as a more efficient water quality monitoring solution but the accuracy of the led-photodiode sensor still requires further development studies